Technologies for Children - Fleer, Marilyn (Cambridge ; Port Melbourne, Vic. : Cambridge University Press, 2016)
Technologies for Children presents a comprehensive array of contextual examples for teaching design and technology to children from birth to twelve years. Aligning with the Australian Curriculum - Technologies, this book focuses predominantly on design technologies, with special reference to digital technologies. It provides both theory and practical ideas for teaching infants, toddlers, preschoolers and primary children.
1. The contexts of technologies and technological knowledge -- 2. Key ideas in the technologies curriculum -- 3. Designing and creating preferred futures -- 4. Creativity in design -- 5. The curriculum in action: digital technologies -- 6. Technologies contexts: food and fibre production and food specialisations -- 7. Technologies contexts-engineering principles and systems, and materials and technologies specialisations -- 8. The curriculum in action: project management -- 9. Planning, assessment and evaluation in technologies -- 10. Planning for teaching technologies: analysing the pedagogical approaches.
Record machine-generated from publisher information.
Includes bibliographical references and index.
Keywords: Philosophy & theory of education; Design and technology -- Study and teaching (Primary) -- Australia